Development of Instagram Promotional Content Management to Increase Customer Engagement on the Social Media Account @Upagordanghealing_Elfrida.Sitohang - Tasya Bernatha Hia; Aprinawati Aprinawati (Economic: Journal Economic and Business, 2025)
This research and development was motivated by the suboptimal management of promotional content on Instagram in increasing customer engagement (likes, comments, and shares) on the @upagordanghealing_elfrida.sitohang account. The purpose of this study was to develop promotional content in the form of photos and videos. This study used the Rapid Application Development (RAD) development model which consists of four main stages: Planning, User Design, Construction, and Cut Over. The subject of the research was the Instagram account @upagordanghealing_elfrida.sitohang, with a total of 30 contents uploaded during the development process. Data collection techniques included observation, interviews, document analysis, and descriptive statistics. A total of 30 new contents (25 videos and 5 photos) were produced and uploaded on a schedule while maintaining a consistent visual identity. After implementation, there was a significant increase in customer engagement, with an Engagement Rate (ER) reaching 169% and a reach of 15%. These findings indicate that good promotional content management can effectively increase audience interest and engagement.